Optimization and Characterization of Cultural Conditions for Higher Production of Xanthan Gum by Xanthomonas Campestris Using Saw Dust Hydrolysate as A carbon Source - Mustafa Mohammad Haider (International Journal of Pharma and Bio Sciences, 2020)
Xanthan gum has many industrial applications due to its unique physiochemical characteristics. Xanthomonas campestris is used to produce xanthan gum at commercial scale. The present study was carried out to stimulate the production of “xanthan gum” by a local isolate of the bacteria Xanthomonase campestris MU1 using saw dust hydrolysate as a carbon source and basal media supplemented with various nitrogen concentrations in the form of ammonium nitrate. The effect of various physiological factors on the production of “xanthan gum” by the bacterium were investigated. The results showed that “xanthan gum” production was affected by the concentration of the carbon and nitrogen sources used in the fermentation media. The highest yield of xanthan gum was 13.7 g/l in the medium containing 40 g/l carbon in the form of sawdust hydrolysate and 0.25 g/l ammonium nitrate as a nitrogen source. Moreover, the production of the “xanthan gum” was stimulated gradually by the addition of citric acid up to 3.5 g/l to reach 14.9 g/l which provided favorable conditions to the fermentation media. Increasing the concentration above 3.50 g/l had inhibitory effect on the biosynthesis of “xanthan gum”. The effect of the rotation speed of the fermentation media on the production “xanthan gum” and its viscosity was also studied. The highest production of “xanthan gum” and its viscosity was increased up to reach 16 g/l and 5.5cP, respectively, in the fermentation medium containing 40 g/l saw dust as a carbon source and 0.25 g/l ammonium nitrate as a nitrogen source and 3.5g/l citric acid at rotation speed of 400 rpm.